STRATEGI GURU PAI DALAM MEMBIMBING PEMBELAJARAN AL-QUR’AN ANAK BERKEBUTUHAN KHUSUS DI SDN 03 PULAI ANAK AIR KOTA BUKITTINGGI - Zira Avelia; Arifmiboy Arifmiboy; Charles Charles; Afrinaldi Afrinaldi (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
As a result of theinterviews conducted, researchers found that the methods used by PAI teachers to guide Al-Qur’an learning for children with special needs at SDN 03 Pulai Anak Air were less effective. The aim of this research is todetermine the methods, obstacles and solutions used by PAI teachers in guiding Al-Qur’an learning for children with special needs at SDN 03 Pulai Anak Air. This research use descriptive qualitative approach. Education Teachers for Children with Special Needs are the main research informants, and other supporting in formants include homeroom teachers, school principals, parents and guardians of children with special needs. Researchers collected data using observation, interviews and documentation techniques. The analysis techniques used by the author are collection, reduction, presentation and drawing conclusions. Researchers used data triangulation techniques to test the validity of their data. According to research, although the PAI teacher’s approach to guiding Al-Qur’an learning for children with special needs at SDN 03 Pulai Anak Air has been used, this approach has not been optimal. Therefore, to guide children with special needs in learning the Koran, they must receive special guidance in a special room.